1990
DOI: 10.1002/1097-0142(19901115)66:10<2099::aid-cncr2820661010>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and ultrastructural study of the ovary in childhood leukemia after successful treatment

Abstract: Ovarian biopsy specimens from ten girls (three postmenarcheal) who had undergone antiblastic treatment for acute lymphoblastic leukemia (ALL) and were in complete remission were examined by light microscope. The biopsy specimens from four of these patients (three postmenarcheal) were also observed by electron microscope. The structural and ultrastructural analysis showed a reduction in the number of follicles which were otherwise normal. No follicles were found in the thin sections from two of the three postme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 21 publications
2
45
1
Order By: Relevance
“…Validating and confirming in vitro organ culture experiments, doxorubicin treatment also resulted in reduced vascular density in xenografted human ovarian tissues compared with controls. These results are consistent with other studies that have demonstrated that chemotherapy may induce stromal fibrosis and o varian vascular abnormalities [18,21].…”
Section: • Impact Of Chemotherapy On Stromal/vascular Function In Ovarysupporting
confidence: 93%
See 2 more Smart Citations
“…Validating and confirming in vitro organ culture experiments, doxorubicin treatment also resulted in reduced vascular density in xenografted human ovarian tissues compared with controls. These results are consistent with other studies that have demonstrated that chemotherapy may induce stromal fibrosis and o varian vascular abnormalities [18,21].…”
Section: • Impact Of Chemotherapy On Stromal/vascular Function In Ovarysupporting
confidence: 93%
“…Validating and confirming in vitro organ culture experiments, doxorubicin treatment also resulted in reduced vascular density in xenografted human ovarian tissues compared with controls. These results are consistent with other studies that have demonstrated that chemotherapy may induce stromal fibrosis and o varian vascular abnormalities [18,21].While it is challenging to demonstrate that vascular damage directly contributes to chemotherapy-induced ovarian damage, in a recent study we showed an inverse correlation between ovarian vascular density and primordial follicles apoptosis [22]. It is normally supposed that primordial follicles do not depend on blood perfusion, but clinical experience from ovarian tissue transplantation do not support this belief [5].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Oocytes/PMF In human fetal ovary exposed to CTX, apoptosis was shown before in oocytes (PMF), than GCs [121] CTX metabolites induce H2AX, a marker of double strand DNA breaks predominantly in mouse oocytes (but also in GCs) cultured in vitro [122] GCs In the GCs of rat ovaries CTX damage to mitochondria induce the release of the cytocrome C into cytoplasm leading to cell apoptosis mediated by caspase family proteins. Damage in human GCs nuclei and follicular basement membranes [32,33,[122][123][124][125][126][127][128][129] Oxidative stress has been associated with CTX toxicity in GCs of mature follicles. CTX induces depletion in glutathione and rise in reactive oxygen species mediating apoptosis in GCs Stromal cells/vessels…”
Section: Mechanism(s) Of Ovarian Toxicity/features Of the Damage Refementioning
confidence: 99%
“…Several studies have documented signs of fibrosis in the cortical stroma, and changes in the capillaries were observed in ovaries exposed to chemotherapy (Marcello et al 1999, Meirow et al 2007, Oktem & Oktay 2007. Using innovative real-time molecular imaging, we observed an acute reduction in ovarian blood flow and disintegration of the vessel wall following in vivo administration of doxorubicin.…”
Section: Ovarian Toxicity Mediated By An Acute Vascular Insultmentioning
confidence: 72%